Simplified access for reduction and fixation of a frontal bone fracture - Pires, Willian Ricardo [UNESP]; Oliveira Puttini, Igor De [UNESP]; Oliva, André Hergesel De [UNESP]; Jacob, Ricardo Garcia Mureb [UNESP]; Figueira Júnior, Heldo Cesar [UNESP]; Sonoda, Celso Koogi [UNESP]; Fabris, André Luis Da Silva [UNESP]; Faverani, Leonardo Perez [UNESP]; Souza, Francisley Ávila [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP] (Wolters Kluwer, 2018)
The frontal bone fractures occur very often in service units in oral and maxillofacial surgery. Bicoronal access is the most common for the surgical treatment of frontal bone fractures. However, patients are surprised when they receive notice that such invasive access will be made. This approach allows adequate visualization of the fracture site, but may be associated with complications, which can be avoided by the use of less invasive techniques. We describe an alternative approach that aims to minimize the complications of a coronal incision.
Keywords: Fracture fixation; internal; orbital fractures; skull fractures